Assessment of ballast layer under multiple field conditions in China. (18th July 2022) - Guo, Yunlong; Wang, Shilei; Jing, Guoqing; Yang, Fei; Liu, Guixian; Qiang, Weile; Wang, Yan
Highlights: Six diverse railway lines were inspected by the GPR, proving the GPR application feasibility for diverse railway line conditions. Accuracy of the GPR-based fouling index is correlated with sieving-based fouling index. By comparing the sensitivity of different indicators, the suitable GPR signal processing means is obtained. Fouling composition is proved as a decisive factor for GPR-based fouling level evaluation, especially the iron ore. Abstract: Ballast layer condition should be more regularly and accurately inspected to ensure safe train operation; however, traditional inspection methods cannot sufficiently fulfil this task. This paper presents a method of ground penetrating radar (GPR) application to reflect ballast layer fouling levels under diverse field conditions (annual gross passing load, cleaning and renewal year, fouling composition and transportation type). The results show that the GPR-based inspection method can assess the ballast layer fouling level with a 1–7% difference from the traditional sieving results. Fouling composition (especially metal materials) has a great effect on the GPR signals, thus affecting the inspection accuracy of ballast layer fouling level. Developing diverse GPR-based fouling indicators (by distinguishing different GPR signal features) can improve the GPR inspection applicability to the diverse field conditions.